2007
DOI: 10.1002/eji.200636485
|View full text |Cite
|
Sign up to set email alerts
|

GATA3 controls the expression of CD5 and the T cell receptor during CD4 T cell lineage development

Abstract: The transcription factor GATA3 is essential at multiple stages of T cell development, including the earliest double-negative stages, b-selection and CD4 single-positive thymocytes. Here, we show that in CD2-GATA3 transgenic mice, with enforced GATA3 expression driven by the CD2 promoter, thymocytes have reduced levels of CD5, which is a negative regulator of TCR signaling participating in TCR repertoire fine-tuning. Reduction of CD5 expression was most prominent in CD4 + CD8 + double-positive (DP) cells and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 37 publications
3
24
1
Order By: Relevance
“…CD2-GATA-3 Tg and DO11.10 × CD2-GATA-3 mice were generated as described earlier. 51 All mice were kept under routine animal housing conditions and experiments were approved by the animal experimental committee of the VUMC or the Erasmus MC.…”
Section: Micementioning
confidence: 99%
“…CD2-GATA-3 Tg and DO11.10 × CD2-GATA-3 mice were generated as described earlier. 51 All mice were kept under routine animal housing conditions and experiments were approved by the animal experimental committee of the VUMC or the Erasmus MC.…”
Section: Micementioning
confidence: 99%
“…However, unlike the Zbtb7b hd mutation, Gata3 disruption arrested the development of MHCII-restricted thymocytes during the DP to CD4 SP transition but did not result in redirection to the CD8 lineage12. Conversely, enhanced Gata3 expression failed to redirect MHCI-restricted thymocytes into the CD4 lineage11,14. These observations led to the conclusion that Gata3 controls a post-commitment differentiation or survival step during CD4 T cell development9,12.…”
Section: Introductionmentioning
confidence: 99%
“…During positive selection, Gata3 expression peaks during the DP to CD4 SP transition, and decreases during the DP to CD8 SP transition10,11. Targeted disruption of Gata3 in DP thymocytes demonstrated that this factor is necessary for the development of CD4 but not CD8 T cells12-14. However, unlike the Zbtb7b hd mutation, Gata3 disruption arrested the development of MHCII-restricted thymocytes during the DP to CD4 SP transition but did not result in redirection to the CD8 lineage12.…”
Section: Introductionmentioning
confidence: 99%
“…In activated Th2 cells GATA3, STAT6, c-Maf and the chromatinremodeling enzyme Brg1 and RNA polymerase II are all bound across the Th2 locus, whereby densely looped, transcriptionally active chromatin is packaged by the special AT-rich sequence binding protein (SATB1) [13]. Furthermore, GATA3 activity is required during embryonic development [14] and at multiple stages of thymocyte development, including the earliest double negative stages [15,16], b-selection [17] and CD4 1 cell development [17][18][19].…”
Section: Introductionmentioning
confidence: 99%